Early boosting of p38 MAPK signaling pathway by lycorine hydrochloride potently inhibits PRRSV proliferation in primary and established cells - Su, Lizhan; Zhang, Zhening; Zhang, Siqi; He, Jiajing; Chen, Yaoqi; Wu, Guohong; Zhang, Zhiying; Chen, Weisan; Zhang, Mingxin; Chen, Jianxin (Frontiers in Microbiology, 2025)
Porcine reproductive and respiratory syndrome virus (PRRSV) has caused tremendous economic losses in the swine industry since emerging in the late 1980s. Although vaccination has been widely used to control PRRS epidemics in Chinese pig farms, they provided limited protection against PRRSV transmission; moreover, no effective therapeutic drugs are available. Therefore, there is an urgent need to develop novel antiviral strategies to control PRRSV epidemics. This study showed that Lycorine hydrochloride (LH), an isoquinoline alkaloid isolated from the bulb of Lycoris radiata herb, potently suppressed PRRSV replication in Marc-145 cells and primary porcine alveolar macrophages ex vivo (PAMs) with 50% effective antiviral concentrations (EC50) less than 1 μM. LH exhibited broad-spectrum inhibitory activities in vitro against clinically circulating type 2 PRRSV GD-HD, CH-1a, and NADC30-like HNhx strains in China. Mechanistically, LH treatment induced a rapid up-regulation of p38 MAPK signaling pathway in both infected and uninfected cells, which enhanced the expressions of NLRP3 and Caspase-1 proteins, thereby promoting the conversion of pro-IL-1β to IL-1β, which led to decreased PRRSV replication. In summary, this study reveals that early boosting of p38 MAPK signaling pathway induced by LH treatment significantly suppresses PRRSV propagation, and LH has the potential to be used as a novel antiviral agent against PRRSV infections.